EFEKTIVITAS KERJA PEGAWAI PERALIHAN JABATAN STRUKTURAL KE JABATAN FUNGSIONAL PADA BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI TENGAH - Nurindayani; Mustainah; Nuraisyah (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Nurindayani (B 102 22 048 ), Thesis Title : Work Effectiveness of Structural Positions Transition to Functional Positions at the Regional Civil Service Agency of Central Sulawesi Province. Under the Supervisions of Mustainah (Head of the Advisory Team) and Nuraisyah, (Supevisor Team).Work Effectiveness of Structural Positions Transition to Functional Positions at the Regional Civil Service Agency of Central Sulawesi Province. This research was conducted in Palu through purposive informant selection techniques. The research method used was descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. Meanwhile, data analysis included data condensation, data display and drawing conclusions and verification. Five aspects of the seven indicators in this research have not worked effectively, namely Quality, Growth, Work Spirit, Motivation and Adaptation Flexibility and two aspects that have been effective are Productivity and Stability.The research results reveals by researchers regarding the work effectiveness of transitioning from structural positions to functional positions at the Central Sulawesi Province Regional Civil Service Agency, researchers concluded by linking Richard M. Steers' theory with indicators as a reference for researchers with five aspects that were not yet effective, namely: Quality, Growth, Work Spirit , Motivation, and Adaptation Flexibility where there are still many employees who have not been able to adapt to the new work system in functional positions due to the lack of employee desire to learn the new work system and lack of coordination and socialization from leadership regarding the work system in functional positions to employees who experience the transition of position. Indicators that have been effective are productivity and stability. This is due to the transition of position employees are placed and given tasks based on their position level.